2016
DOI: 10.14791/btrt.2016.4.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Brain Tumor Patients Treated with Surgery: Preliminary Result of a Single Institution

Abstract: BackgroundAlongside the extent of removal and patients’ survival in the management of brain tumors, health-related quality of life (HRQOL) has become an important consideration. The purpose of this study is to evaluate the change of HRQOL in brain tumor patients before and after surgery and to assess the associated factors that contribute to the change of HRQOL.MethodsA total of 258 patients who underwent surgical treatment were enrolled in this study. The European Organization for Research and Treatment of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
1
9
0
10
Order By: Relevance
“…It has been calculated using one population mean formula, based on a SD range of 12.7–34.1, 5% level of significance with precision of 2.5, and by adjusting the sample size for 10% non-response rate. The minimum sample size has been estimated to be 250 32–35…”
Section: Methodsmentioning
confidence: 99%
“…It has been calculated using one population mean formula, based on a SD range of 12.7–34.1, 5% level of significance with precision of 2.5, and by adjusting the sample size for 10% non-response rate. The minimum sample size has been estimated to be 250 32–35…”
Section: Methodsmentioning
confidence: 99%
“…A study by Kim et al showed that global quality of life and emotional function were significantly improved, but physical function was aggravated, especially for dyspnea, communication deficit, and leg weakness. Quality of life was mostly influenced by financial difficulty and future uncertainty [7]. A study by Kuhlthau et al from 142 children (aged 2-18 years) with brain tumor and completed treatment protocol also showed similar result.…”
Section: Discussionmentioning
confidence: 77%
“…Interpretasi nilai kualitas hidup mengikuti Lee dkk dan Kim dkk yang mendapatkan hasil bahwa nilai >50 untuk masing-masing skala fungsional dan kualitas hidup pada EORTC QLQ-C30 menunjukkan kualitas hidup yang baik, sedangkan nilai >50 untuk masing-masing skala keluhan pada EORTC QLQ-C30 dan EORTC QLQ-BN20 menunjukkan kualitas hidup yang buruk. 12,16 Selanjutnya dilakukan penilaian hubungan antara masing-masing karakteristik demografi dan tumor primer intrakranial dengan nilai skala kualitas hidup yang didapat pada EORTC QLQ-C30, untuk mengetahui peran tiap karakteristik terhadap kualitas hidup. 16 Analisis data yang dilakukan secara umum bersifat deskriptif yang diolah dengan program SPSS versi 24.0 for Windows.…”
Section: Kualitas Hidupunclassified
“…12,16 Selanjutnya dilakukan penilaian hubungan antara masing-masing karakteristik demografi dan tumor primer intrakranial dengan nilai skala kualitas hidup yang didapat pada EORTC QLQ-C30, untuk mengetahui peran tiap karakteristik terhadap kualitas hidup. 16 Analisis data yang dilakukan secara umum bersifat deskriptif yang diolah dengan program SPSS versi 24.0 for Windows. Adanya hubungan antara karakteristik demografi dan tumor intrakranial dengan kualitas hidup dianalisis dengan menggunakan tabulasi silang menggunakan uji Chi-square.…”
Section: Kualitas Hidupunclassified
See 1 more Smart Citation